1998
DOI: 10.1021/jo981322c
|View full text |Cite
|
Sign up to set email alerts
|

Oxoammonium Salts. 6.1 4-Acetylamino-2,2,6,6-tetramethylpiperidine-1-oxoammonium Perchlorate:  A Stable and Convenient Reagent for the Oxidation of Alcohols. Silica Gel Catalysis

Abstract: 4-Acetylamino-2,2,6,6-tetramethylpiperidine-1-oxoammonium perchlorate, 1, is a stable, nonhygroscopic oxoammonium salt that is easily prepared and can be used for the oxidation of alcohols to ketones or aldehydes in near quantitative yields. The reaction is colorimetric, does not require anhydrous conditions, does not involve heavy metals, and can be carried out conveniently. Furthermore, the oxidant can be easily regenerated. The oxidation is somewhat specific in that the relative reactivities of an allyl alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
169
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 169 publications
(174 citation statements)
references
References 38 publications
4
169
0
1
Order By: Relevance
“…Amines, phosphines, phenols, and anilines can also be oxidized with nitroxides. Active oxammonium salt 2 can be isolated and used as a stoichiometric oxidant with the judicious choice of a counterion, 17 or more commonly it is formed in situ from catalytic nitroxide with the aid of a primary oxidant. 12,[14][15][16]23,[94][95][96][97][98][99][100][101] Ma and Bobbitt 102 demonstrated that alcohols can be oxidized by oxammonium salts (3) generated by the acid-promoted disproportionation of excess TEMPO (Scheme 3).…”
Section: Nitroxide Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Amines, phosphines, phenols, and anilines can also be oxidized with nitroxides. Active oxammonium salt 2 can be isolated and used as a stoichiometric oxidant with the judicious choice of a counterion, 17 or more commonly it is formed in situ from catalytic nitroxide with the aid of a primary oxidant. 12,[14][15][16]23,[94][95][96][97][98][99][100][101] Ma and Bobbitt 102 demonstrated that alcohols can be oxidized by oxammonium salts (3) generated by the acid-promoted disproportionation of excess TEMPO (Scheme 3).…”
Section: Nitroxide Backgroundmentioning
confidence: 99%
“…These unusual properties have led to a wide range of applications spanning their use in biology as spin labels [1][2][3][4][5][6] to the development of organomagnetic materials. 7 In organic chemistry, nitroxides have been used in kinetic studies, [8][9][10][11] as oxidizing species in the form of the corresponding N-oxo ammonium salts, [12][13][14][15][16][17][18][19][20][21][22][23] as temporary caps for transient carbon radicals, [24][25][26][27][28][29][30][31] and as probes for stereocontrol with prochiral carbon radicals. [32][33][34][35][36] In polymer chemistry, nitroxide-mediated polymerization (NMP) [37][38][39][40][41][42][43][44][45][46][47] has become popular as a method for preparing living polymers ...…”
Section: Introductionmentioning
confidence: 99%
“…The latter is prepared from cyclopentadiene by an easily scalable, three-step procedure involving a Prins reaction with formaldehyde, selective allylic oxidation with the reagent developed by Bobbitt, and protection of a primary alcohol. [5,6] Silyl enol ether formation from 4 may be accomplished under either soft (R 3 SiOTf, NEt 3 ) or hard (lithium diisopropylamide, R 3 SiCl) enolization reaction conditions. [7] In this way, the tert-butyldimethylsilyl (TBS), triethylsilyl, or trimethylsilyl enol ethers may be prepared, with the former being preferred because of the increased hydrolytic stability of the diene and the subsequent cycloadducts.…”
mentioning
confidence: 99%
“…1 In addition to being more sustainable, these salts have several advantages: 1) the spent oxidant is easily recovered and recyclable; 2) oxidations are performed under mild conditions and are simple to conduct; 3) oxidations are typically colorimetric processes and reaction progress can be monitored visually. 2 …”
Section: Introductionmentioning
confidence: 99%